2017
DOI: 10.4236/oalib.1103168
|View full text |Cite
|
Sign up to set email alerts
|

White Water Kayaking Risk: Malaysian Perspective

Abstract: White water kayaking is the fun sport on fast moving water, typically call white water river. The element of fun and challenge has attracted many people to join this adventure sports in Malaysia. This study examined the risk in adventure sport tourism by white water kayakers in Malaysia. The objective of this study is to reveal the injuries suffered by whitewater kayakers during activity. This 2013 survey will be described using descriptive data only. The survey forms were distributed via kayak clubs and assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Recent data from Laver et al (2017), suggested that the risk and severity of injury in global adventure tourism was unexpectedly high with approximately 70% of the total injury rate was recorded. Meanwhile in Malaysia, Zakaria et al (2017) and Majeedkutty et al (2017) documented that 85.7% and 83.8% respectively experienced injuries during adventure activities in their report. This high percentage of total injury rate from the recent report, proved that risk in adventure tourism is genuine.…”
Section: Injury and Incidents In Adventure Tourismmentioning
confidence: 91%
“…Recent data from Laver et al (2017), suggested that the risk and severity of injury in global adventure tourism was unexpectedly high with approximately 70% of the total injury rate was recorded. Meanwhile in Malaysia, Zakaria et al (2017) and Majeedkutty et al (2017) documented that 85.7% and 83.8% respectively experienced injuries during adventure activities in their report. This high percentage of total injury rate from the recent report, proved that risk in adventure tourism is genuine.…”
Section: Injury and Incidents In Adventure Tourismmentioning
confidence: 91%
“…Moreover, the determination of anaerobic parameters in elite kayakers has been studied, shedding light on the physiological demands of the sport [12]. Additionally, the hearth risk associated with white water kayaking has been examined, emphasizing the need for safety considerations in extreme water sports [13,14]. Finally, the relationship between performance tests and body composition/physical strength characteristics in sprint canoe and kayak paddlers has been explored, providing insights into the physical attributes associated with performance [15].…”
Section: Introductionmentioning
confidence: 99%